2012
DOI: 10.1177/0017896912452071
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-based behavioural interventions for health: A systematic review

Abstract: Objective: To perform a systematic review of the literature concerning behavioural mobile health (mHealth) and summarize points related to heath topic, use of theory, audience, purpose, design, intervention components, and principal results that can inform future health education applications. Design: A systematic review of the literature. Method: Thirty-four interventions published in peer-reviewed journals before July 2010, employing a short message service (SMS) and/or multimedia message service to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 37 publications
0
99
0
1
Order By: Relevance
“…Although there are studies investigating the use of apps on mobile devices in MANUSCRIPT ACCEPTED -BRAIN INJURY: 02 FEBRUARY 2017 18 rehabilitation for other health conditions [133][134][135], there is limited research evaluating the use of these technologies with people after a TBI [72,136,137] -identified in one systematic review [72]. Lee et al (2015) tested the use of mobile devices and apps in concussion management [72].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are studies investigating the use of apps on mobile devices in MANUSCRIPT ACCEPTED -BRAIN INJURY: 02 FEBRUARY 2017 18 rehabilitation for other health conditions [133][134][135], there is limited research evaluating the use of these technologies with people after a TBI [72,136,137] -identified in one systematic review [72]. Lee et al (2015) tested the use of mobile devices and apps in concussion management [72].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%
“…[132]. Although there are studies investigating the use of apps on mobile devices in rehabilitation for other health conditions [133][134][135] [72]. The authors highlighted the current lack of regulation and high variability of the apps available for concussion assessment, which led to development of a consumer checklist to assist in choosing an appropriate concussion assessment app [72].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%
“…In particular there is limited information regarding the best application characteristics for disadvantaged populations (5). There have been a number of early systematic reviews that examine the efficacy of health application interventions; however, these either focus on weight loss rather than nutrition improvement (10)(11)(12)(13)(14), exclude qualitative and descriptive studies (15,16), and/or include text messaging and Web-based interventions (10,12,13,(16)(17)(18), with none specifically relating to community settings.…”
Section: Introductionmentioning
confidence: 99%
“…This can be expensive and pose a barrier to the adoption of new behaviours because the behaviour is learnt in isolation, in non-habitual settings and out of context to the problems experienced by the patient (Rosser et al, 2009). There is evidence to suggest that clinicians are now considering new approaches and technologies such as mobile apps for health conditions to engage service users in treatments and interventions in order to facilitate behaviour change (Chomutare et al, 2011;Buhi et al, 2013;Nundy et al, 2014;Direito et al, 2014;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%